Rare occurrence of the liver metastases at the HBsAg positive patients operated due to colorectal cancer - Perz, Hanna; Paszkowski, Jacek; Szmeja, Jacek; Drews, Michał; Migdalski, Paweł; Pyda, Przemysław; Banasiewicz, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2001)
During neoplastic disease of the gastrointestinal tract in 15-40% of the operated patients the metastatic changes in the liver are found. Little is known about the mechanism of metastatisation and secondary tumour growth. The local immunological status and metabolic level of this organ play an important role for implantation of free neoplasmatic cells. The aim of the study was to correlate a frequency of liver metastases in two groups of the patients operated due to colon and rectum cancer in our Department between 1983 and 1998. The first group consisted of HBs antigen positive patients (n=36), the second group consisted of the HBs antigen negative patients (n=867). To determine the HbsAg we used EIA method. In the first group we observed a metastatic changes in the liver in 4 patients (11,1%), in the second group metastatic tumour (s) was found in 204 operated patients (23,5%). Metastatic tumours were found rarely in the group with HbsAg positive (p = 0,08).